Effect of Speed of Adjustments on Capital Structure Decision: A Conceptual Analysis - Damina, Emmanuel Kukah; Muritala, Taiwo; Ibrahim, Abbas Umar (International Journal of Economics and Financial Issues, 2022)
This study conceptually examines the effect of speed of adjustments on capital structure decisions. The study provides a conceptual and theoretical underpinning focused on the review of several studies on the effect of speed of adjustments on capital structure decisions. The study discovered firm size, assets, growth, profitability, and other factors that influence the speed of adjustments. The findings from a prior study showed that estimators of the speed of adjustments include the regression analysis, generalized methods of moments (GMM) and stochastic frontier analysis (SFA) models without a predictive model. The study recommends for a generalized predictive model that determines the speed of adjustments to the optimum capital structure of firms.